Shaping social behavior in an enriched environment - Amorim, Liliana; Dá Mesquita, Sandro; Jacinto, Luís; Castelhano-Carlos, Magda J.; Santos, Nadine Correia; Leite-Almeida, Hugo; Sousa, Nuno (Frontiers in Behavioral Neuroscience, 2022)
Access to vital needs shapes social orders. In rats, social systems tend to maintain a certain stability, but alterations in the physical environment can change inter-individual relations, which consequently can alter social orders. Principles governing social systems are, however, difficult to study and most analyses have been restricted to dyads of animals over short periods of time, hardly capturing the complexity and temporal dynamics of social interactions. Herein, we studied social interactions in a colony of six rats living in a customized enriched environment (PhenoWorld, PhW), under variable conditions of access/availability to limited resources. Reductions in food accessibility and availability resulted in a marked heterogeneity in sniffing, chasing and fighting/struggling behaviors, and, in the latter condition, an overall increase of these displays. The introduction of the possibility of interaction with a female rat also increased the amount of sniffing and fighting/struggling in a homogeneous manner. Results also showed that individual food retrieval success had no association with fighting/struggling when food pellets are delivered to the animals. However, there was a statistically significant correlation between fighting/struggling and impulsivity as measured by the amount of premature responses in the Variable-to-Signal-Test outside of the PhW providing external validation to our measures. To sum up, through continuous monitoring of a group of rats in the PhW, we demonstrated how variations in access to reinforcers modulate social behavior.